Predictors of rehospitalization among older adults: Results of the CRIME Study. Issue 10 (21st November 2016) - Sganga, Federica; Landi, Francesco; Volpato, Stefano; Cherubini, Antonio; Ruggiero, Carmelinda; Corsonello, Andrea; Fabbietti, Paolo; Lattanzio, Fabrizia; Gravina, Ester Manes; Bernabei, Roberto; Onder, Graziano
Abstract : Aim: To assess the predictors of readmission among older adults hospitalized in acute care wards. Methods: A prospective cohort study was carried out among 921 hospitalized older adults participating in the CRiteria to Assess Appropriate Medication Use among Elderly Complex Patients (CRIME) project. The primary outcome of the study was rehospitalization within 1 year after discharge from acute care hospitals. We assessed the participants with a questionnaire including 350 items about demographic, social and clinical characteristics. We analyzed all factors at discharge that could be considered predictors of readmission. Results: The mean age of the participants was 81.2 years (SD 7.4 years), and 509 were women (55.3%). Overall, 280 of 921 patients (30.4%) were rehospitalized during the 1‐year follow up of the study. Patients with a Mini‐Mental State Examination score equal to or higher than 24 had a higher probability of rehospitalization, as compared with those who performed lower than 24 (OR 1.76, 95% CI 1.04–2.83). In addition, heart failure (OR 1.77, 95% CI 1.14–2.24), the number of falls during 1‐year follow up (OR 1.15, 95% CI 1.05–1.28) and the number of drugs during first hospitalization (OR 1.15, 95% CI 1.01–1.07) were significantly associated with rehospitalization, whereas no significant association was shown for age, sex and walking speed for minimum size (OR 1.15, 95% CI 0.99–2.00). Conclusions: Predictors of readmission in older people are an intact cognitive status; the presence of a geriatric condition, such as heart failure and falls; and a high number of drugs during first hospitalization. Further studies are required to assess the impact of home care for avoiding readmission in patients with an intact cognitive status, and supporting and treating patients with dementia.Geriatr Gerontol Int 2017; 17: 1588–1592.